Application Of Participatory Communication By Women Leaders In Protecting Forests In East Sumba (Case Study Of The Sumba Savanna Community In Demonstration) - Deviyanti, Diyah; Utami, Eulis (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Sumba's forests provide water, food security, indigenous and cultural roots, habitat for endemic flora and fauna, and a setting for Marapu ritual beliefs. In 2017, a sugar company suddenly seized customary community land, one of which was the land of the Praing Umalulu indigenous people in Umalulu District, East Sumba Regency, NTT. The large role of forests in the lives of indigenous peoples in East Sumba made a woman lead a women's solidarity movement and establish the Sabana Sumba community to fight the sugar company. This resistance action could not be separated from the communication built by its organizer, Rambu Dai Mami. The purpose of this study was to find out how the application of participatory communication by women leaders in protecting forests in East Sumba through case studies in the Sabana Sumba community in demonstrations. The focus of this research uses a qualitative descriptive approach and is analyzed on the application of four participatory communication indicators: heteroglossia, dialogical, polyphony, and carnival. The techniques used for data are interviews and documentation. Data analysis used Miles and Huberman's interactive model for data analysis. The results of the research are the application of participatory communication by women leaders in protecting forests in East Sumba through case studies in the Sabana Sumba community in demonstrations that have been carried out and have succeeded in getting indigenous people to move to take demonstrations against sugar companies. The heteroglossia indicator shows socialization through discussions regarding the impacts of land and environmental changes from several angles, such as economic, social, and cultural factors that complement each other there. Dialogical indicators show success in making indigenous women and the leaders of the 33 kabihu in Praing Umalulu aware and moving against them with demonstrations. The polyphony indicator shows that there are no differences of opinion, but there have been attempts at weakening from the sugar factory companies, but this has actually made the indigenous peoples stronger and more solid. Carnival indicators show that when Sabana Sumba leaders socialize, they create a welcoming environment with humor, there are snacks and drinks such as coffee or tea, and there are also betel nuts to eat together both during socialization and during demonstrations that are obtained independently from the community.